Depredation and acorn germination ability of three seed sources for Quercus suber L. in Mediterranean environment - Younsi, Salah Eddine; Adjami, Yasmine; Ghanem, Rym; Bouchaib, Billel; Ouakid, Mohamed Laid (Annals of Silvicultural Research, 2022)
The cork oak is a major forest species that occupies a limited natural area in the Mediterranean region. Unfortunately, it is a patrimony that continues to deteriorate under the effect of many factors, leading to the disappearance of large forest areas. Its decline is caused by abiotic factors, including climate change, wildfire, and biotic factors such as invasive species, and pests. In addition, the species faces regeneration difficulties because of lack of forest conservation. We respond to these problems by studying the germination of acorns, as this constitutes the first and crucial phase of vegetative development. We then considered some biotic and abiotic interactions, including the effect of provenance (altitude gradient), health status and biometrics of acorns. The results indicate that there is variability in acorn biometrics by site, that there are no significant correlations between the health status of the acorns and their biometrics, and that carpophageal insects can attack different acorns regardless of their calibre or weight. For germination, healthy acorns with a wider calibre are much better favoured. The impact of acorn depredation on germination is dependent on its intensity: a single perforation, for example, was not found to influence germination; beyond that, this impact becomes significant.